Competitive Intelligence and Small Business Sustainability in a Precarious Working Environment: Evidence from Selected Cleaning Services Companies in Lagos State - J. O. Ekwoaba; Emmanuel Uwem (Unilag Journal of Humanities, 2019)
Small businesses are continuously seeking for better insight for their capacity to competeeffectively due to competitive pressures from new sources and faster dissemination ofboth innovation and imitation facilitated by forces of globalisation. However, variousstudies have shown that most small businesses in Nigeria experience inconsistency inservice delivery, employment stability and barely survive a few years after inception. Thisis a threat to economic growth as small businesses account for about over 50% of GDPof any country. Advancing adequate reasons for small business failure in Nigeria hasposed a serious challenge over the years. This study aimed at examining the effect ofcompetitive intelligence on small business sustainability in selected cleaning servicescompanies in Lagos State. A survey research design, stratified sampling technique andsimple regression analysis were used for this study. A well-structured questionnaire wasadministered to the respondents who consist of top executives, supervisors and cleanersworking in the selected cleaning services companies in the three senatorial districts(Lagos Central and Lagos East districts consisting of five local government areas, whileLagos West district consist of ten local government areas) in Lagos State and offeringjanitorial services only. A sample size of 400 respondents was arrived at using a Rao softsample size calculator out of the total population of 1535 personnel. The hypotheses weretested using simple linear regression. Statistical analysis was carried out using SPSS. Thestudy found that competitive intelligence had a significant effect on small businesssustainability in the selected cleaning services companies in Lagos State (B=0.606; R2=.357; p<0.05). The study recommended implementation of organisational justice aspanacea for retaining quality human capital capable of sourcing the requisiteinformation needed for strategic decision making and business sustainability. In addition,businesses should adopt human resource policies and practices that could elicitinformation from both the internal and external environment.